Assessment of the methodology for the CFD simulation of the flight of a quadcopter UAV. Issue 218 (November 2021) - Paz, C.; Suárez, E.; Gil, C.; Vence, J.
Abstract: The computational fluid dynamics (CFD) simulation is gaining attraction in the development of modern unmanned aerial vehicles (UAV), but few research has been made on quadcopters and the characterisation of the flows generated by the propellers, which determine the thrust capacity. Therefore, the purpose of this study is to assess the performance in the 3D flow simulation of the most promising methods: multiple reference frames (MRF) and sliding meshes. Additionally, the effect of the ground proximity has been included. The results for a sole propeller revealed both models as equivalent with respect to the evaluation of the ground effect, even though a noticeable deviation was observed in the thrust quantification. In the case of quadcopters, the relative position between blades and frame was proved as a key factor. Thus, similar rates of thrust change were obtained when minimising the superposition of the blade over the body arms in the MRF case. However, the thrust magnitude differed at least 11% at any simulated position. Assuming this deviation, the significantly lower computational cost of the MRF turns this model into a very interesting option. Finally, the influence of the relative blade-to-blade position in the sliding simulation was also assessed. Highlights: The 3D flow under a drone was simulated considering the effect of ground proximity Multiple reference frames (MRF) and sliding meshes were tested. For a sole propeller, both models are equivalent with respect to the ground effect The relative blade-to-blade position was assessed in the sliding simulation In quadcopters the thrust differed at least 11% at any position for both CFD models